1998
DOI: 10.1046/j.1365-2141.1998.00920.x
|View full text |Cite
|
Sign up to set email alerts
|

Haematological response of patients with myelodysplastic syndrome to antithymocyte globulin is associated with a loss of lymphocyte‐mediated inhibition of CFU‐GM and alterations in T‐cell receptor Vβ profiles

Abstract: Summary.We have demonstrated that 44% of myelodysplastic syndrome (MDS) patients with cytopenia have a haematological response to antithymocyte globulin (ATG). Three ATG responders and two non-responders with refractory anaemia were further studied for lymphocytemediated inhibition of bone marrow using a standard CFU-GM assay. In responders, peripheral blood lymphocytes (PBL) added at a 5:1 ratio suppressed CFU-GM by 54 Ϯ 9% (P ¼ 0·04) and was reversed by ATG treatment. Pre-treatment marrow depleted of CD3 lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
126
1
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(135 citation statements)
references
References 22 publications
2
126
1
6
Order By: Relevance
“…2,3 Investigations of immunosuppressive therapies have shown that a subset of MDS patients experience sustained erythroid improvement with response rates ranging from 15 to 45%. [4][5][6][7][8][9][10][11][12] Univariant and multivariant statistical analyses have identified clinical and biological features associated with clinical response to immunosuppressive therapy, which served as the basis for the generation of response predictive models. [4][5][6][13][14][15][16][17][18] In these analyses, bone marrow hypocellularity, HLA-DR15 phenotype, younger age, lower platelet count and shorter duration of transfusion requirement were associated with response to immunosuppressive therapy.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Investigations of immunosuppressive therapies have shown that a subset of MDS patients experience sustained erythroid improvement with response rates ranging from 15 to 45%. [4][5][6][7][8][9][10][11][12] Univariant and multivariant statistical analyses have identified clinical and biological features associated with clinical response to immunosuppressive therapy, which served as the basis for the generation of response predictive models. [4][5][6][13][14][15][16][17][18] In these analyses, bone marrow hypocellularity, HLA-DR15 phenotype, younger age, lower platelet count and shorter duration of transfusion requirement were associated with response to immunosuppressive therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Despite being a heterogeneous group of disorders based on the diverse morphologic, genetic, biologic, and clinical characteristics, they all derive from a molecular defect (an intrinsic or acquired primary event) in the hematopoietic progenitor cells (HPC) (1). Multiple altered extrinsic factors have concomitantly been described: (1) those affecting the BM microenvironment (2) and (2) T cell autoimmunemediated myelosuppression (3)(4)(5). Another biological observation is an increase in BM cell apoptosis.…”
mentioning
confidence: 99%
“…Most previous work has focused on the role of lymphocytes in this process. Autologous T cells inhibit growth of progenitor cells in MDS, 2,3 and this effect can disappear after successful treatment with ATG. 2 A role of immune-mediated suppression of hematopoiesis has been most extensively defined in trisomy 8 MDS.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous T cells inhibit growth of progenitor cells in MDS, 2,3 and this effect can disappear after successful treatment with ATG. 2 A role of immune-mediated suppression of hematopoiesis has been most extensively defined in trisomy 8 MDS. Consistent with what was shown for the general population of MDS patients, 4,6,7 Sloand et al 5 have demonstrated that expanded clonal populations of T cells can be found in all patients with trisomy 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation